Validation of the Australian Football League Player Ratings. Issue 6 (December 2018) - McIntosh, Sam; Kovalchik, Stephanie; Robertson, Sam
This study investigated the validity of the official Australian Football League Player Ratings system. It also aimed to determine the extent to which the distribution of points across the 13 rating subcategories could explain Australian Football League match outcome. Ratings were obtained for each player from Australian Football League matches played during the 2013–2016 seasons, along with the corresponding match outcome (Win/Loss and score margin). The values for each of the 13 subcategories that comprise the ratings were also obtained for the 2016 season. Total team rating scores were derived as an objective team outcome for each match. Percentage agreement and Pearson correlational analyses revealed that winning teams displayed a higher total team rating in 94.2% of matches and an association of r  = 0.96 (95% confidence interval = 0.95–0.96) between match score margin and total team rating differential, respectively. A Partial Decision Tree (PART) analysis resulted in seven rules capable of determining the extent to which relative contributions of rating subcategories explain Win/Loss at an accuracy of 79.3%. These models support the validity of the Australian Football League Player Ratings system and its use as a pertinent system for objective player analyses in the Australian Football League.